Penatalaksanaan Nipple Inverted dengan Jarum Suntik Terbalik pada Ibu Menyusui - Wahyuningsih, Dwi Suryanti; Marsum, Marsum; Widyawati, Melyana Nurul (Journal of Telenursing (JOTING), 2024)
This research aims to identify effective and innovative techniques that can be used to treat inverted nipples in breastfeeding mothers. The method used is literature using the PICO technique including: (1) Population: breastfeeding mothers; (2) Intervention: inverted nipple technique; (3) Comparison does not exist; (4) Outcome: prominent nipples. The database used is Evidence Based Practice (EBP) from the Google Scholar data base. The results of the research show that there are 5 articles that mention several efforts that can be made in the management of inverted nipples, including the use of skill vacuum therapy, modification of injection syringes, reverse syringe technique, breast care, pulling the nipple using the thumb, and forefinger and the nipple retractor method. It was concluded that the inverted nipple management method affected the nipple shape of breastfeeding mothers and the dominant technique was the technique with an inverted syringe. Keywords: Effective, Mother, Breastfeeding, Inverted Nipple, Technique